Morphology-based investigation of differences between spoken and written isiZulu (Journal of the Digital Humanities Association of Southern Africa, 2022)
Research attempting to describe and quantify the differences between spoken and written language has been done for languages such as English, but not for isiZulu. In this paper, we present a quantitative investigation into such differences by considering the morphology of tokens in a transcribed spoken isiZulu corpus and a written isiZulu corpus. We use morpheme tags as a proxy for features that typically differ between spoken and written language, and calculate relative differences of the occurrence of specific morpheme tags from analyses produced by ZulMorph, a finite-state morphological analyser for isiZulu. This analysis presents information that could inform the development of voice-enabled computer applications for isiZulu.
Keywords: spoken language; written language; voice computing; isiZulu